Sponsor message processing in live broadcasts—A pilot study on the role of game outcome uncertainty and emotions - Christoph Breuer; Christopher Rumpf; Felix Boronczyk (Psychology & Marketing, 2021)
Live sport broadcasts can evoke emotions in consumers and allow companies to reach their audience in environments that allow for automatic processing of brand messages. However, only few studies have applied psychophysiological methodologies to assess how the live nature of a competition and viewers' emotions affect the processing of sponsor messages, and prior research has mostly relied on ex-post data. Therefore, to identify the interplay of game outcome uncertainty, viewers' emotions and attention to sponsor messages, this exploratory lab study tracks continuous viewer data during live sport broadcasts. Soccer fans' (n0.167em=0.167em11) arousal, emotional valence, and visual attention to sponsors while watching live soccer broadcasts were measured using galvanic skin response, video-based facial expressions, and infrared eye-tracking. In-play betting odds served as an indicator of outcome uncertainty. Multi-level modeling reveals that greater outcome uncertainty increases arousal and the magnitude of emotional response. Further, the data reveal that low-to-moderate arousal and valence-neutral emotional states increase viewer attention to sponsor messages. This study is the first to consider the dynamics of live sports experiences in the explanation of sponsorship effectiveness. It contributes to the literature by using continuous measurements involving psychophysiological data to investigate emotions and attention to sponsors.
Keywords: 650; arousal; emotions; eye-tracking; outcome uncertainty; sponsorship; visual attention